2020
DOI: 10.1016/j.surfcoat.2020.125464
|View full text |Cite
|
Sign up to set email alerts
|

Surface functionalization of 3D printed structures: Aesthetic and antibiofouling properties

Abstract: Additive manufacturing (AM) is a hot topic nowadays, having a first order in importance in research trends, improving existent technologies and carrying them further. AM can be applied to ceramics, which have importance in current technologies. Their capability to maintain functional properties for long time periods, combined with the easiness to process and the abundance of raw materials, make them a fundamental part of mankind development. Within ceramics, stoneware has a wide range of uses but in some condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…The XRD pattern of TiN coating indicates that the most intense peaks are located at 36.8 • and 42.9 • , which are very close to the TiN (111) and TiN (200) peaks. Previous studies in TiN-Ag coatings deposited by magnetron sputtering reported this behavior [19,24].…”
Section: Structural Analysismentioning
confidence: 64%
“…The XRD pattern of TiN coating indicates that the most intense peaks are located at 36.8 • and 42.9 • , which are very close to the TiN (111) and TiN (200) peaks. Previous studies in TiN-Ag coatings deposited by magnetron sputtering reported this behavior [19,24].…”
Section: Structural Analysismentioning
confidence: 64%
“…To control the O/N ratio and consequently tune the colour pallet, a duty cycle controller was used with 45 s period in a square wave for O 2 addition on the reactive atmosphere. The duty cycle used in this study was the same as that used in previous studies by the authors [15] and which has been explained in previous these studies [23][24][25][26][27]. The O 2 duty cycle set-ups were 20, 40, 80 (exclusively for Zr(O)N system) and 100% (only in Cu added films), which correspond to the flow values and times shown in table 1.…”
Section: Methodsmentioning
confidence: 98%
“…By adding carbon, the colour shifted towards black tones. In fact, in a previous study [15], the authors of this investigation reported the same colour shifting in Ti(O)N coatings and also ZrN x O y coatings [16]. They revealed four distinct zones in Zr(O)N system: Zone I and II, where coatings were based on ZrN and performed a wide colour pallet from pale yellow or golden tones to dark blue; Oxynitrides (zone III) and oxides (zone IV), which presented a semitransparent optical behaviour.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations